The degree of achieving of private schools For quality standards from the point of view of teachers (Damascus University Journal of educational and Psychologyical sciences, 2025)
The goal of the current research is to determine the degree of achieving of private schools for quality standards from the point of view of the teachers who teach in them. To achieve this purpose, the descriptive method was used, and a sample of teachers consisting of (155) male and female teachers was selected, In the academic year 2023/2024 in the second semester, and the hypotheses were tested in the variables (gender, academic qualification, teaching experience).A questionnaire was prepared to achieve this purpose according to six areas (student affairs, teacher performance, teaching and learning methods, evaluation, communication with the local community, and infrastructure) to demonstrate the extent to which quality standards have been achieved in the performance of private schools.The results showed that the degree of achieving of private schools according to quality standards was high in all fields, and in the field of infrastructure the highest degree. The results showed that there were differences according to the gender variable in favor of females, and there were no differences according to the academic qualification variable, and there were differences according to the teaching experience variable in favor of teachers experienced (5-10).The research presented a set of proposals, including the importance of cooperation between the public and private sectors in the field of education, benefiting from the services provided by private schools in cooperation with the Ministry of Education, and conducting the necessary research to develop educational work.
Keywords: Achieving Dgree; Quality standards; Private schools; Teachers